2005
DOI: 10.1007/s11178-005-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Mobility of Substituted 2-Methoxychalcones under the Action of Lanthanide Shift Reagents

Abstract: Various lanthanide shift reagents Ln(fod) 3 were found to affect the conformational composition of 2-methoxychalcones. Coordination of Yb(fod) 3 occurs mainly at the carbonyl oxygen atom of the substrate, while Eu(fod) 3 and shift reagents derived from other lanthanides coordinate substituted chalcones as bidentate ligands, giving rise to a secondary tetrachelate with the corresponding change of conformation of the substrate molecule. The possibility for chelation is determined by steric hindrances in the vici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…25a–b,27 It is also reported that different coordination modes of Eu(fod) 3 and Yb(fod) 3 may account for their different facial selectivity in HDA reaction. 26 As depicted in Figure 3, the high facial selectivity induced by Yb(fod) 3 is probably ascribed to the different facial steric surrounding. The 7,20-epoxy blocks the α -face, and consequently, the dienophile approaches to the heterodiene mainly from the less hindered β -face in an endo -selective manner.…”
Section: Resultsmentioning
confidence: 96%
“…25a–b,27 It is also reported that different coordination modes of Eu(fod) 3 and Yb(fod) 3 may account for their different facial selectivity in HDA reaction. 26 As depicted in Figure 3, the high facial selectivity induced by Yb(fod) 3 is probably ascribed to the different facial steric surrounding. The 7,20-epoxy blocks the α -face, and consequently, the dienophile approaches to the heterodiene mainly from the less hindered β -face in an endo -selective manner.…”
Section: Resultsmentioning
confidence: 96%
“…Lanthanide (III) complexes, in particular, of the chelate type, are used as tools in the structural analysis with the help of NMR spec-troscopy [1,2]. The LSRs are widely applied when studying the structure of organic compounds, their conformations in solutions, and the enantiomeric purity, as well as to detect the chirality, and so forth [3].…”
Section: Introductionmentioning
confidence: 99%
“…5 The most common practice is to successively add known amounts of LSR to the compound under study and record NMR spectra aer each addition (the shied spectra). 1,[5][6][7][8][9][10][11] In recent years experiments involving chiral LSRs have been successfully carried out for the enantiomeric discrimination of oxygenated bicyclic monoterpenes (bornyl acetate, fenchone and camphor) contained in essential oils, without isolation of the compounds. 3 This approach has been successfully employed in structural and conformational analysis of many synthetic organic compounds and natural products, as well as in the study of their chirality, but it requires the substrate in pure state with known or almost resolved structure on the basis of data from regular NMR measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The application of LSRs is based on their ability to selectively coordinate electron-donor functional groups in the substrates and induce shis of signals in NMR spectra. 5 The most common practice is to successively add known amounts of LSR to the compound under study and record NMR spectra aer each addition (the shied spectra). The chemical shis of some protons and carbons in the substrates alter, to a greater or lesser degree, with each addition of LSR and may result in the segregation of overlapping signals that could facilitate its assignments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation